TMET-12. HYPERPOLARIZED Δ- [1-13C] GLUCONOLACTONE IMAGING VISUALIZES TERT-ASSOCIATED CHANGES IN DYNAMIC PENTOSE PHOSPHATE PATHWAY METABOLISM IN GLIOBLASTOMA. (14th November 2022) - Minami, Noriaki; Hong, Donghyun; Taglang, Celine; Batsios, Georgios; Gillepspie, Anne Marie; Stevers, Nicholas; Viswanath, Pavithra; Costello, Joseph F; Ronen, Sabrina
Abstract: BACKGROUND: TERT promoter mutations are a hallmark of glioblastoma (GBM). We recently reported that the expression of TERT and its upstream transcriptional factor, GABPB1, are strongly correlated with redox in GBM with TERT promoter mutations. However, further imaging biomarkers which visualize redox-associated metabolism and TERT expression are needed. Here we demonstrate that 13 C magnetic resonance spectroscopy (MRS) of hyperpolarized δ-[1- 13 C] gluconolactone metabolism is a useful imaging tool to visualize changes in dynamic pentose phosphate pathway (PPP) metabolism that reflect TERT-associated changes in redox in GBM. METHODS: U251 human GBM cells stably expressing shRNA targeting TERT or GABPB1 were compared to controls. Doxycyclin-inducible shTERT or shGABPB1 U251 cells were also examined. For in vivo studies, cells were injected into immunodeficient rat brains and tumors confirmed by T2-weighted MRI. δ-[1- 13 C] gluconolactone was polarized using a Hypersense DNP polarizer and injected into live cells or tumor-bearing rats. For cells 13 C-MRS was acquired using a 500MHz Agilent spectrometer and analyzed using Mnova and Matlab software. For in vivo 13 C-MRS studies, spectra were acquired using a 3T Bruker scanner and a spectral spatial echo-planar spectroscopic imaging sequence. Spectral signal to noise was improved using Tensor denoising. Spectra were processed using a custom-written Matlab script. RESULTS: Hyperpolarized 6-phosphogluconolactone (6PG), the metabolic product from δ-[1- 13 C] gluconolactone via the PPP, was significantly reduced in TERT or GABPB1 silenced cells compared to control cells in both U251 models. The positive correlation between TERT expression and 6PG level was confirmed by linear regression analysis. Hyperpolarized 6PG production in both tumor models was also significantly reduced in TERT or GABPB1-silenced tumors compared to controls. CONCLUSION: We successfully visualized TERT-associated changes in dynamic PPP metabolism in a GBM model in cells and in vivo . Hyperpolarized δ-[1-13C] gluconolactone is a potential tool for monitoring TERT expression in GBM with TERT promoter mutations.